Figure of 3-sign: a case report. Issue 1 (27th December 2018) - Henzel, Agata Wiktoria; Schwerzmann, Markus
Abstract: Background: A 50-year-old mother of four children was newly diagnosed with arterial hypertension and bilateral neck pulsations. Case summary: Her current blood pressure was 170/100 mmHg in the right arm and 122 mmHg systolic in the right ankle. There was a radio-femoral delay palpable. The electrocardiogram showed signs of left ventricular hypertrophy. On the chest X-ray, a figure of 3-sign was found at the aortic knuckle and notching of the inferior ribs was present. An echocardiogram showed concentric left ventricular hypertrophy, a mildly stenotic bicuspid aortic valve, and a low peak-gradient across the descending aorta. Magnetic resonance imaging demonstrated severe focal coarctation with complete interruption of the descending aorta. Large collaterals vessels were present, effectively bridging the aortic interruption. Discussion: In light of the extensive collateral vessels and the bleeding risk, an extra-anatomic aortic bypass was considered the least risky procedure. The patient agreed to the intervention and had an uncomplicated surgical course and recovery. At the 12-month follow-up, she was doing well and normotensive on Lisinopril 5 mg OD.